Pengaruh Shopeepay Terhadap Perilaku Konsumtif Mahasiswa Prodi Pendidikan Ekonomi Universitas Hamzanwadi Angkatan 2021 - Nuha, Aulia; Zein, Rohaeniah (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2024)
This study aims to analyze the impact of the use of the ShopeePay digital wallet on the consumptive behavior of students from the Economics Education Study Program at Universitas Hamzanwadi, Class of 2021. The research methodology applied in this study is a descriptive quantitative approach. The subjects of the study consist of 65 students from the Class of 2021 in the Economics Education Program. The sample was selected using purposive sampling, and data was collected through questionnaires. To analyze the data, the researcher used Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) method to examine the relationships between the existing indicators. The model analysis results showed that the developed model is very good, with an R-square value of 0.961, meaning that 96.1% of the variation in consumptive behavior can be explained by the use of ShopeePay. Hypothesis testing was conducted using the bootstrapping method to evaluate the significance of the relationships between the indicators. The evaluation findings indicate that the use of ShopeePay has a positive and strong impact on students' consumptive behavior, as evidenced by a t- statistic value of 235.954 > 1.96 and a p-value of 0.000 < 0.05